1993
DOI: 10.1093/cvr/27.9.1619
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5-hydroxytryptamine in the progression of monocrotaline induced pulmonary hypertension in rats

Abstract: The present study suggests that 5-HT released from platelets contributes to the initiation and progression of monocrotaline induced pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 0 publications
3
28
0
Order By: Relevance
“…Platelet activation is enhanced in patients with primary pulmonary hypertension (Farber and Loscalzo, 1999), and intravascular thrombosis has also been observed both in patients and in model systems. Moreover, experimentally induced thrombocytopenia reduces the development of pulmonary hypertension (Kanai et al, 1993). In this study, staining for thrombocytes (␣IIb␤3) and fibrinogen showed platelet deposition and thrombosis in the pulmonary vasculature of wild-type hypoxic mice.…”
Section: Cox-gene Disruption and Pulmonary Hypertension 55supporting
confidence: 55%
“…Platelet activation is enhanced in patients with primary pulmonary hypertension (Farber and Loscalzo, 1999), and intravascular thrombosis has also been observed both in patients and in model systems. Moreover, experimentally induced thrombocytopenia reduces the development of pulmonary hypertension (Kanai et al, 1993). In this study, staining for thrombocytes (␣IIb␤3) and fibrinogen showed platelet deposition and thrombosis in the pulmonary vasculature of wild-type hypoxic mice.…”
Section: Cox-gene Disruption and Pulmonary Hypertension 55supporting
confidence: 55%
“…Plasma levels of 5-HT were significantly increased in PAH patients and rodent models. 9,20,46 We also showed that circulating 5-HT level was elevated in MCT-induced PAH rats ( Figure S1, available in the online-only Data Supplement). It remains unclear that, in PAH models and patients, the elevation in circulating 5-HT and the upregulation of 5-HT2BR which comes first.…”
Section: -Ht2brmentioning
confidence: 64%
“…A previous pathophysiological review identified several lines of evidence to suggest a relationship between thrombotic arteriopathy and PAH [1]. Abnormalities of the activated clotting system [17][18][19], impaired fibrinolysis [20,21], abnormal platelet function [22,23] and histological evidence of microvascular thrombosis [24,25] have been associated with animal models and patients with IPAH. Thus, there is a biologically plausible rationale for anticoagulation therapy in these patients, with the goals of preventing progression of disease, decreasing Ppa, and improving symptoms and prognosis [1].…”
Section: Discussionmentioning
confidence: 99%